2018
DOI: 10.1002/ets2.12196
|View full text |Cite
|
Sign up to set email alerts
|

A Simulation Study to Compare Nonequivalent Groups With Anchor Test Equating and Pseudo‐Equivalent Group Linking

Abstract: In this paper we compare the newly developed pseudo‐equivalent groups (PEG) linking method with the linking methods based on the traditional nonequivalent groups with anchor test (NEAT) design and illustrate how to use the PEG methods under imperfect equating conditions. To do this, we proposed a new method that combines the features of PEG linking and NEAT equating (referred as PEGAT) and compared it with NEAT and PEG. PEG mainly uses test takers' background variables to create PEG and then links scores on di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…Sansivieri and Wiberg (2017) obtained similar results by using covariates with IRT observed score linking. Lu and Guo (2018) showed that the use of the minimum discriminant information to create pseudoequivalent groups before equating in a NEAT design reduced equating error compared to linking without using the additional background information. In the present study, linking through a weak anchor led to only small bias because the degree of deviation from group equivalence was rather small.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sansivieri and Wiberg (2017) obtained similar results by using covariates with IRT observed score linking. Lu and Guo (2018) showed that the use of the minimum discriminant information to create pseudoequivalent groups before equating in a NEAT design reduced equating error compared to linking without using the additional background information. In the present study, linking through a weak anchor led to only small bias because the degree of deviation from group equivalence was rather small.…”
Section: Discussionmentioning
confidence: 99%
“…With an established testing program that uses common items for equating, Haberman verified that PEG linking produces results similar to the conventional linkings with anchor tests. As an extension of the PEG modeling, Lu and Guo (2018) further proposed the use of both background information and anchor test scores to adjust for group ability differences. Using simulated data, they showed that the linking based on common items could be improved by incorporating the PEG adjustment procedure into the NEAT process.…”
mentioning
confidence: 99%
“…The finding that weighted equating led to better equating results than the unweighted equating were consistent with other research on the use of common‐item equating with covariates (i.e., background variables correlated with the test scores). For example, Bränberg and Wiberg (2011) showed that the use of covariates such as gender and education with linear equating had less equating error than the regular linear equating without the use of the covariates; Sansivieri and Wiberg (2017) showed reduced equating error by using covariates in the IRT observed score equating context; and Lu and Guo (2018) showed that the use of the minimum discriminant information method to create equivalent groups along with the NEAT design had less equating error than the equating without the additional background information.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…With an established testing program that uses common items for equating, he verified that PEG linking produces results similar to the conventional equatings with anchor tests. As an extension of the PEG modeling, Lu and Guo (2018) further proposed to use both background information and anchor test scores to adjust group ability difference. With simulation studies based on real data, they showed that the equating based on common items could be improved by incorporating the PEG adjustment procedure into the NEAT process.…”
mentioning
confidence: 99%
“…Several psychometricians at ETS conducted research to assess the practical implications of PEG for large‐scale assessment programs using either real or simulated data (see Kim & Lu, 2018; Lu & Guo, 2018; Oh et al, 2015; Xi et al, 2015). A recent empirical investigation (Kim, 2020) using certification tests demonstrated how the PEG approach could be used to explore potential mode effects across RP and TC delivery.…”
mentioning
confidence: 99%